Community Empowerment at Cirendeu Cassava MSMEs Based on the Penthahelix Collaboration Model - Sukma, Arindha; Rusmiati, Viena; Sardin, Sardin (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
MSMEs are an important part of the economy in Indonesia, marked by their contribution in reducing unemployment by absorbing labor. Cassava Multipurpose MSMEs in Cirendeu Traditional Village are also required to be able to innovate in marketing and product innovation produced in order to remain competitive against changing times. Some of the problems of Cirendeu's Multipurpose Cassava MSMEs are still in terms of the limitations of MSME actors to innovate such as the lack of innovation in processed products from cassava, still traditional packaging and conventional marketing. MSME development needs to be carried out in improving and fostering competitive capabilities. Therefore, the involvement of various actors will help the development run optimally. Through pentahelix synergy, which is cooperation between stakeholders consisting of academy, business, government, community, and media. This research aims to find out and describe community empowerment with the pentahelix model in the development of MSMEs. The method used in the research is descriptive qualitative through interviews, documentation and literature study. The results showed that the development of MSMEs has involved five actors in the pentahelix model, namely academics, business, community, government, and media.